Aplikasi Visual Novel Biografi Joko Widodo - Hendi Setiawan; M Dwi Kurnia Lubis (LPPM Sekolah Tinggi Teknologi Indonesia Tanjungpinang, 2022)
Visual Novel is one of the literature interactive in the form of a game or a media to convey a story that is made in the form of an application. Visual Novels can also make various choices that affect the outcome of the storyline. The visual form of this application is usually in the form of illustrated images which are usually combined with background music and voice actors. When designing the Visual Novel Biography of Joko Widodo, the author will use the Rapid Application Development (RAD) development method. The application was developed based on an existing prototype through Ren'py, then developed based on needs, user design, construction and Cutover. The result to be achieved is to create an interesting application that can increase someone's interest in reading or in general the low reading intention of the Indonesian people into an interesting form of application media.